Prioritized e-mail servicing to reduce non-spam delay and loss: a performance-cost analysis - Marsono, Muhammad Nadzir; El-Kharashi, M. Watheq; Gebali, Fayez (John Wiley & Sons, Ltd, 2007)
This paper proposes a prioritized e-mail servicing on e-mail servers to reduce the delay and loss of non-spam e-mails due to queuing. Using a prioritized two-queue scheme, non-spam e-mails are queued in a fast queue and given higher service priority than spam e-mails that are queued in a slow queue. Four prioritized e-mail service strategies for the two-queue scheme are proposed and analyzed. We modeled these four strategies using discrete-time Markov chain analysis under different e-mail traffic loads and service capacities. Non-spam e-mails can be delivered within a small delay, even under heavy e-mail loadings and high spam-to-non-spam a priori. Results from our analysis of the two-queue scheme show that it gives non-spam delay and loss probability two orders of magnitude smaller than the typical single-queue approach during heavy spam traffic. Moreover, prioritized e-mail servicing protects e-mail servers from spam attacks.